PENGEMBANGAN MEDIA PEMBELAJARAN WEBCOMIC FISIKA WEBTOON UNTUK SISWA SMP PADA POKOK BAHASAN HUKUM NEWTON - Kusumasari, Widyaloka; Darmadi, I Wayan; Saehana, Sahrul (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
his study aimed to determine the feasibility level of the physics webtoon webcomic produced by media and material experts, and teachers, as well as to determine the student's response to the use of the physics webtoon webcomic produced. This type of research wa research and development, R & D (Research and Development) using the 4-D model. The results showed that the feasibility test assessment by both experts and teachers was in the very good category and was suitable for learning media for students. The results of the feasibility test data analysis to the media expert validator, material expert and teacher indicated that the acquisition of an average assessment score of 3.82 out of 4 or in "very good" category, then 3.45 of 4 or in "very good" category, and 3.89 out of 4 or in “Very Good” category respectively. The results of the analysis of student response assessments showed that students strongly agree that comics were interesting and feasible to be used as learning media. The results of the student response data analysis showed an average score of 3.54 out of 4 or in "strongly agree" category. Overall, it indicated that the webtoon physics was very good and feasible to be used as an attractive (alternative) learning media for students.